Optimized culturing yields high success rates and preserves molecular heterogeneity, enabling personalized screening for high-grade gliomas - Cassandra Posthoorn-Verheul; Federica Fabro; Ioannis Ntafoulis; Chelsea den Hollander; Iris S. C. Verploegh; Rutger Balvers; Trisha V. Kers; Jessica Hoogeveen; Judith van der Burg; Bert Eussen; Annelies de Klein; Kate J. Feller; et al. (npj Precision Oncology)
Abstract To discover new treatment options for high-grade glioma (HGG), robust in vitro models are essential, but reliably establishing patient-derived cell cultures remains challenging. We established glioma stem-like cell (GSC) cultures from 114 consecutive HGG specimens via traditional surgical resection and/or ultrasonic aspiration, using completely dissociated single cell (single cell-derived, SCD) and partially dissociated 3D-derived (3DD) tissue fragments. Higher success rates in culture establishment were obtained from ultrasonic aspirates and 3DD surgical samples. Combining these approaches yielded a 96% success rate. Copy number profiling showed overall genetic similarities between cultures and parental tissue. Single-cell sequencing revealed greater transcriptomic heterogeneity in ultrasonic aspiration-derived cultures. Our protocol enabled the screening of 20 anti-cancer agents within a clinically relevant timeframe for 16 out of 18 HGG samples. This refined protocol serves as a robust tool for establishing HGG cell cultures that retain the molecular characteristics of the tumors and support applications in precision medicine.